2017
DOI: 10.1186/s12913-016-1931-3
|View full text |Cite
|
Sign up to set email alerts
|

Health outcomes of bedaquiline in the treatment of multidrug-resistant tuberculosis in selected high burden countries

Abstract: BackgroundLess than one-third of patients who are estimated to be infected with multidrug-resistant tuberculosis (MDR-TB) receive MDR-TB treatment regimens, and only 48% of those who received treatment have successful outcomes. Despite current regimens, newer, more effective and cost-effective approaches to treatment are needed. The aim of the study was to project health outcomes and impact on healthcare resources of adding bedaquiline to the treatment regimen of MDR-TB in selected high burden countries: Eston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…The scenario analyses performed in the empirical study could only inform decision makers on the cost drivers of implementing the bedaquiline-based regimens. As observed in other studies, the use of bedaquiline mainly reduced the hospitalization costs due to the rapid culture conversion that allowed early discharge from inpatient care [27][28][29]. The study also showed significant cost saving due the elimination of costs for the management of injectable-related adverse events.…”
Section: Discussionsupporting
confidence: 71%
“…The scenario analyses performed in the empirical study could only inform decision makers on the cost drivers of implementing the bedaquiline-based regimens. As observed in other studies, the use of bedaquiline mainly reduced the hospitalization costs due to the rapid culture conversion that allowed early discharge from inpatient care [27][28][29]. The study also showed significant cost saving due the elimination of costs for the management of injectable-related adverse events.…”
Section: Discussionsupporting
confidence: 71%
“…(6) Cohort‐based Markov models and cohort‐based decision‐analytic model have demonstrated it is cost‐effective to add bedaquiline to a background MDR‐TB treatment regimen…”
Section: Mdr‐tb: Repurposed and Novel Drugsmentioning
confidence: 99%
“…To add to the benefits of including BDQ in the anti-TB regimens a study was done using the cohort-based Markov state transition model simulated for a period of 10 years. This assessed the health and economic effects of the background regimen (BR) with or without BDQ and concluded that adding BDQ to BR provides improvements in health outcomes and reductions in healthcare costs in high MDR-TB burden countries [33]. As per CDC guidelines, BDQ can be effectively included into the anti-TB drug regimen to treat MDR infected children when ''an effective treatment regimen cannot otherwise be provided'' [34].…”
Section: The Recent Concernsmentioning
confidence: 99%